The quilting circle [large type] - Lillard, Amy (Lillard, Amy. Wells Landing series, 2018)
United by faith, and bonded by their quilting circle, the Amish women of Wells Landing, Oklahoma are there for one another through all life's joys and challenges. Youngest quilter Clara Rose Yutzy is planning her wedding to her longtime beau--which is why she resolutely ignores newly warm feelings for her best friend, Obidiah. But Obie is certain God intends them to be together. With the Lord's help, he'll prove to Clara Rose how much he loves her. Mariana Miller prayed for a child throughout fifteen years of marriage. But now, newly widowed, Mariana discovers she's pregnant--with twins! She's more grateful than ever for her caring community--especially Reuben Weisel, her late husband's business partner and best friend. Reuben's quiet strength comforts her--until he proposes marriage. Tess Smiley is new to Wells Landing and newly married. But her marriage isn't the harmonious union she envisioned. Tess loves Jacob with all her heart, but her heart tells her she must take a stand--and ask for support. Only then does Jacob see how he has hurt her. But is he too late?